Dynamic cobble berm revetments: the state of the practice and a proposed design process - Bond, Hailey G.; Wengrove, Meagan E.; Blenkinsopp, Chris E.; Bayle, Paul M.; Kaminsky, George M.; Allan, Jonathan C.; Michalsen, David R.; Ostrow, Kayla S.; Moritz, Hans Rod (Frontiers in Marine Science, 2025)
Chronic coastal erosion is a recurring issue that threatens the built environment and the stability of public beaches. Dynamic cobble berm revetments, which replicate natural composite beaches, are a possible option for nature-based erosion mitigation on high-energy coastlines. Dynamic cobble berm revetments are composed of a sandy foreshore and an engineered cobble berm, which evolves over time while dissipating wave energy. While dynamic cobble berm revetment projects have been constructed over the past two decades, there remains a lack of engineering guidance for many aspects of their design. In this study, we summarize the current state of the practice for the design of dynamic cobble berm revetments. We first present a review of tools that have been used for dynamic cobble berm revetment design, including their basic assumptions and potential limitations. Following, we summarize the design and performance of five dynamic cobble berm revetment projects on the outer coast of the Pacific Northwest, USA, as case studies. Based on the findings of the first two sections, an informal survey of local practitioners, and the knowledge of the author group, we propose a design process for dynamic cobble berm revetments. The design process is not prescriptive, rather, it is intended to give engineers a framework to apply existing tools until the body of dynamic revetment research can support a more prescriptive design guidance. Finally, we evaluate our confidence in the suggestions and tools in the design process, so that engineers and other practitioners can understand the limitations of the current state of the practice.